The Responsability of States for Environmental Harm in a Multinational Context — Problems and Trends - Brunnée, Jutta (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1993)
The paper begins with a discussion of parallels between problems of environmental liability law at the national and international levels. At both levels, rules built upon concerns and priorities of another era had to be applied to the complex environmental problems of our times. Both systems have proven to be inadequate in addressing modern environmental concerns and have evolved to better meet the challenge. The second part of the paper will highlight the shortcomings of the international system and the law of state responsibility. They are rooted in the system's focus on the interests of sovereign states and include the vagueness of the relevant rules, the disagreement as to the standard of liability (fault or strict liability), the perception of many polluting activities as « lawful », the system's reactive character, the system's failure to effectively deal with ecological costs rather than injury to state interests. In its third part, the paper will survey developments and trends that may provide solutions to the aforementioned problems. Possible solutions include the emergence of rules that protect the common interests of the international community rather than the sovereign interests of states, the development of special liability regimes for more narrowly defined environmental concerns (generally : ultrahazardous activities), efforts of the International Law Commission to develop a risk liability regime, the proliferation of regimes designed to prevent or manage environmental problems.